Development of Ethnomathematics-Based Questions on Relations and Functions - Astuti Astuti; Hasnah Faizah; M.Nur Mustafa; Elmustian Elmustian; Hemandra Hemandra (Pendidikan Matematika Universitas Muhammadiyah Bangka Belitung, 2023)
Mathematics learning is expected to be linked to culture, known as Ethnomathematics. Although ethnomathematics-based teaching materials can be found in modules and worksheets, there are few ethnomathematics-based questions on the specific material, particularly relations and functions. This research aims to generate valid and practical ethnomathematics questions for the material on relationships and functions. Tjeerd Plomp's research and development methodology was used in this study, which consists of three stages: preliminary research, prototyping, and assessment. The participants in this study were eighth-grade Islamic junior high school students. This study's instruments included interview sheets, questionnaires, and tests. The validity and practicality of the product are the product's evaluation criteria for development. The validators declared the questions valid based on a validity criterion greater than 0.9 based on the validation. As a result, the questions are valid regarding content, language, and culture. Furthermore, the analysis demonstrates that the questions developed meet practical criteria. The student practicality questionnaire data analysis revealed that each indicator's percentage ranged between 82.14% and 92.8%.